2020
DOI: 10.1177/2473011420s00226
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Tranexamic Acid in Total Ankle Arthroplasty

Abstract: Category: Ankle; Other Introduction/Purpose: Tranexamic acid (TXA) has been shown to significantly reduce blood loss in patients undergoing total knee arthroplasty and total hip arthroplasty. However, there is a paucity of data regarding its safety and efficacy in total ankle arthroplasty (TAA). In light of expanding indications for TAA and its growing utilization, there is a need for more data regarding interventions such as TXA that may reduce perioperative complications and improve patient outcomes for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This comes to a significant importance in foot and ankle procedures with high risk of wound complications such as open reduction and internal fixation of calcaneal fractures and total ankle arthroplasty (TAA). 8,26 In this meta-analysis, TXA was associated with lower overall wound complications: 7% compared with 11% in the control group. Unfortunately, we could not perform a direct comparative subanalysis of wound complications because of the low incidence and variability in reported data.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This comes to a significant importance in foot and ankle procedures with high risk of wound complications such as open reduction and internal fixation of calcaneal fractures and total ankle arthroplasty (TAA). 8,26 In this meta-analysis, TXA was associated with lower overall wound complications: 7% compared with 11% in the control group. Unfortunately, we could not perform a direct comparative subanalysis of wound complications because of the low incidence and variability in reported data.…”
Section: Discussionmentioning
confidence: 73%
“…In a retrospective study by Steinmetz et al 22 that included 119 patients who underwent total ankle arthroplasty, there was no difference in intraoperative blood loss between TXA and control groups. Similarly, a retrospective chart review by Ghobrial et al 8 found that total amount of calculated blood loss did not differ between the treatment and control group ( P > .05). On the contrary, Nodzo et al 16 reported that drain output was significantly less in TXA group compared to that of control group (71.6 ± 60.3 vs 200.2 ± 117.0 mL, respectively, P < .0001).…”
Section: Discussionmentioning
confidence: 84%
“…The PRISMA guidelines state that all systematic reviews should include unpublished literature to avoid positive outcome bias. Therefore, we believe that the inclusion of the abstract by Ghobrial et al 1 in our study was valid and adherent with guidelines and did not introduce a substantial bias. Ultimately, we feel the inclusion of these studies in our analysis mildly increased the bias of the study but did not impact the overall findings significantly.…”
mentioning
confidence: 56%
“…A lack of a control group severely limits the study’s validity due to the unelimination of the placebo effect. The inclusion of the non–peer-reviewed abstract of Ghobrial et al 3 may be a methodological disadvantage with a potential source of bias. The result of hemoglobin (Hgb) changes in this meta-analysis was greatly influenced by this article’s finding as an outlier, which is assumed to lead to concluding no significant improvement in Hgb levels in the TXA group.…”
mentioning
confidence: 99%